Extracellular Vesicles in Physiology, Pathology, and Therapy of the Immune and Central Nervous System, with Focus on Extracellular Vesicles Derived from Mesenchymal Stem Cells as Therapeutic Tools - Koniusz, Sylwia; Andrzejewska, Anna; Muraca, Maurizio; Srivastava, Amit K.; Janowski, Miroslaw; Lukomska, Barbara (Frontiers in Cellular Neuroscience, 2016)
Extracellular vesicles (EVs) are membrane-surrounded structures released by most cell types. They are characterized by a specific set of proteins, lipids and nucleic acids. EVs have been recognized as potent vehicles of intercellular communication to transmit biological signals between cells. In addition, pathophysiological roles of EVs in conditions like cancer, infectious diseases and neurodegenerative disorders are well established. In recent years focus has been shifted on therapeutic use of stem cell derived-EVs. Use of stem cell derived-EVs present distinct advantage over the whole stem cells as EVs do not replicate and after intravenous administration, they are less likely to trap inside the lungs. From the therapeutic perspective, the most promising cellular sources of EVs are mesenchymal stem cells (MSCs), which are easy to obtain and maintain. Therapeutic activity of MSCs has been shown in numerous animal models and the beneficial paracrine effect of MSCs may be mediated by EVs. The various components of MSC derived-EVs such as proteins, lipids and RNA might play a specific therapeutic role. In this review, we characterize the role of EVs in immune and central nervous system (CNS); present evidences for defective signalling of these vesicles in neurodegeneration and therapeutic role of EVs in CNS.